Soluções técnicas de abastecimento de água e modelos de gestão: um estudo em quinze localidades rurais brasileiras - Marielle Aparecida de Moura Raid (2017)
Rural sanitation, historically, was not prioritized by Brazilian public policies, which has led to a shortage of attendance for rural populations, a violation of human rights and health risks, for which sanitation is considered a determinant and conditioning factor. Faced with the absence and deficiency of structural and structurant actions in rural sanitation, together with the incipience of studies focused on this theme, the present work, developed jointly and integrated the research Studies for the conception, formulation and management of the National Rural Sanitation Program, had the objective of proposing technical solutions for water supply and management models adapted to the peculiar and diverse social, environmental, economic and cultural characteristics of Brazilian rural areas. To that end, fifteen case studies were selected by the PNSR coordination team, considering the five Brazilian macro-regions and the different types of rural communities. In these communities, the situational diagnosis related to basic sanitation, using only the data pertinent to water supply. The diagnosis was based on the qualitative research method called Grounded Theory, using qualitative techniques: direct observation, semi-structured interviews, talking map, group interviews and documentary analysis. This methodology was defined by anthropologist and researcher Oscar Torretta in conjunction with the PNSR coordination team. The workshop with specialists was used to choose the technical solutions of water supply appropriate to the local characteristics studied. A consultation was also made to specialists, using an electronic questionnaire, to identify the management models best suited to serving rural contexts. The multicriteria decision support method AHP (Analytic Hierarchy Process) was chosen to handle the questionnaire data. The diagnosis of the case studies confirmed the absence of public authority actions regarding water supply in rural areas. The limitations and precariousness shown revealed the non-compliance of the Human Right to water with regard to quality and safety, availability, physical accessibility, financial accessibility and acceptability, as well as the need to disseminate and exchange knowledge. The technical solutions of water supply were proposed considering the habits and cultures of the populations as well as the environmental and demographic characteristics of the localities and aspects related to the management of the solutions. Collective water supply solutions for agglomerated populations were indicated, such as surface water capitation, full-cycle treatment and network distribution and individual alterative solutions for dispersed populations such as capitation in groundwater, filtration and disinfection and internal channeling. Regarding the management models, the hierarchy of adequacy indicated municipal management and shared management as models better suited to rural contexts. The management model for private companies was the one with the least adjustment, which shows that management in rural areas can not follow a mercantilist logic